Toward Full Zigzag-Edged Nanographenes: Peri-Tetracene and Its Corresponding Circumanthracene - Ajayakumar, M. R.; Fu, Yubin; Ma, Ji; Hennersdorf, Felix; Komber, Hartmut; Weigand, Jan J.; Alfonsov, Alexey; Popov, Alexey A.; Berger, Reinhard; Liu, Junzhi; Muellen, Klaus; Feng, Xinliang (Journal of the American Chemical Society, 2018)
Zigzag-edged nanographene with two rows of fused linear acenes, called as n-peri-acene (n-PA), is considered as a potential building unit in the arena of organic electronics. n-PAs with four (peri-tetracene, 4-PA), five (peri-pentacene, 5-PA) or more benzene rings in a row have been predicted to show open-shell character, which would be attractive for the development of unprecedented molecular spintronics. However, solution-based synthesis of open-shell n-PA has thus far not been successful because of the poor chemical stability. Herein we demonstrated the synthesis and characterization of the hitherto unknown 4-PA by a rational strategy in which steric protection of the zigzag edges playing a pivotal role. The obtained 4-PA possesses a singlet biradical character (y0 = 72%) and exhibits remarkable persistent stability with a half-life time (t1/2) of ∼3 h under ambient conditions. UV-vis-NIR and electrochemical measurements reveal a narrow optical/electrochemical energy gap (1.11 eV) for 4-PA. Moreover, the bay regions of 4-PA enable the efficient 2-fold Diels-Alder reaction, yielding a novel full zigzag-edged circumanthracene.
CRIS-Team Scopus Importer:2023-03-20